2017
DOI: 10.1039/c7sm00813a
|View full text |Cite
|
Sign up to set email alerts
|

The behavior of hydroxide and hydronium ions at the hexadecane–water interface studied with second harmonic generation and zeta potential measurements

Abstract: By probing the electric potential at the hexadecane-water interface with second harmonic generation and the zeta potential at the surface of a hexadecane droplet in its emulsion, we show that hydronium ions don't have a specific affinity to the oil-water interface although hydroxide ions do. The observed apparent affinity of the hydronium ions to the hexadecane-water interface is more likely a result of the electro-static attraction effect. The adsorption free energy of the hydroxide ions at the oil-water inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 64 publications
3
17
0
Order By: Relevance
“…In summary, we determined the effect of ionic strength on the SFG spectra of the surfacebound waters at the silica/water interface through deconvolution of the spectra into surface-bound water, or 𝜒 𝑆 (2) , and diffuse layer water, or 𝜒 (3) 𝑔 3 , components. In lieu of a calculated surface potential for the analysis, we obtained the zeta potential from streaming current measurements, which has been related to both SFG [77][78] and SHG, [79][80][81] but not used to deconvolute the 𝜒 𝑆 (2) and 𝜒 (3) contributions. With the reported phase-sensitive SFG 32 and SHG 31 measurements of the silica/water interface as reference, we applied the maximum entropy method to our measured SFG intensities to obtain the complex SFG spectra.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, we determined the effect of ionic strength on the SFG spectra of the surfacebound waters at the silica/water interface through deconvolution of the spectra into surface-bound water, or 𝜒 𝑆 (2) , and diffuse layer water, or 𝜒 (3) 𝑔 3 , components. In lieu of a calculated surface potential for the analysis, we obtained the zeta potential from streaming current measurements, which has been related to both SFG [77][78] and SHG, [79][80][81] but not used to deconvolute the 𝜒 𝑆 (2) and 𝜒 (3) contributions. With the reported phase-sensitive SFG 32 and SHG 31 measurements of the silica/water interface as reference, we applied the maximum entropy method to our measured SFG intensities to obtain the complex SFG spectra.…”
Section: Discussionmentioning
confidence: 99%
“…Tian and Shen using phase-sensitive sum frequency vibrational spectroscopy showed that the OH – has the highest adsorption energy compared to those of H 3 O + and Cl – at a water–silane interface . A study with second harmonic generation spectroscopy showed that hydroxide ions exhibit affinity for the water–oil interface . Wu et al used second harmonic generation spectroscopy to report that the water–oil interface is negatively charged and described the role of the interfacial electric field in particle adsorption .…”
mentioning
confidence: 99%
“…In summary, we determined the effect of ionic strength on the SFG spectra of the surfacebound waters at the silica/water interface through deconvolution of the spectra into surface-bound water, or (2) , and diffuse layer water, or (3) 3 , components. In lieu of a calculated surface potential for the analysis, we obtained the zeta potential from streaming current measurements, which has been related to both SFG [77][78] and SHG, [79][80][81] but not used to deconvolute the (2) and (3) contributions. With the reported phase-sensitive SFG 32 and SHG 31 measurements of the silica/water interface as reference, we applied the maximum entropy method to our measured SFG intensities to obtain the complex SFG spectra.…”
Section: Discussionmentioning
confidence: 99%